LEAN MASS, AGE AND SCLEROSTIN LEVELS INFLUENCE BONE HEALTH IN POSTMENOPAUSAL WOMEN WITH TYPE 2 DIABETES - Othman, Mazra; Mohamed, Wan Mohd Izani Wan; Mohamed, Mafauzy; Tan, Vina PS (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Osteoporosis affects 1-in-3 women aged 50 years and above. However, studies reported that people with type 2 diabetes (T2D) have more incidences of fractures than nonT2Ds. Yet, few T2D women were osteoporotic. This study aims to describe the osteoporosis status and investigate sclerostin (a signaling protein exclusively from osteocytes that prevent bone formation), lean mass and other related factors to osteoporosis in postmenopausal Malaysian women with T2D. METHODOLOGY We recruited 71 postmenopausal women (age 59.7±4.2 year) and measured their bone mineral density (BMD, kg/cm2 ), body fat (kg) and lean mass (LM, kg) using dual energy X-ray absorptiometry (DXA) and derived BMD T-scores. We obtained fasting blood measures of HbA1c (%), glucose (mmol/L) and sclerostin (pmol/L). Participants’ calcium intake was also assessed using a validated food frequency questionnaire. We conducted correlation followed by multivariable regression analysis using SPSS version 24. RESULTS We detected only seven osteoporotic women (10%) with T-scores <-2.5 and average BMD of 1027.6±87.4 g/cm2 . From our correlation analyses, age (r=-0.28), LM (35.2±5.6 kg, r=0.47) and sclerostin levels (49.4±17.0 pmol/L, r=0.25) were significantly correlated to T-score whereas daily calcium intake (256.7±243.2 mg), menopausal age (51.4±4.1 y), years of T2D (12.3±7.6 y) and HbA1c (9.08±2.3 %) were not significantly correlated. The multivariable regression model predicted 29% (F=9.01, p<0.001) of T-score outcomes from age, LM and sclerostin levels (0.081 muscle + 0.014 sclerostin – 0.07 age – 0.693). CONCLUSION One-in-ten postmenopausal T2D women were osteoporotic from our study. More in-depth investigations are needed to understand these novel results of sclerostin and lean mass influence on bone status in T2D postmenopausal women.